Veterinary Medicine and Problem-Based Learning (PBL): an experience applied to the disciplines of Microbiology and Immunology (Research, Society and Development, 2020)
Problem-Based Learning (PBL) is a teaching and learning methodology that uses everyday professional problems from different areas, to motivate learning for the future performance of academics as professionals and citizens. Thus, in order to enable students of the Veterinary Medicine Course to understand the relationships between the contents of Microbiology and Veterinary Immunology, after some reflections, the need for interdisciplinary activities arose. In this sense, the objective of the present work is to present a case study on the use of the ABP method as an active methodology in the Veterinary Medicine course. For this, a problem situation was elaborated, relating the immunological diagnoses, which are common in veterinary clinical practice and the characteristics of the etiological agent in question, in this case bacteria of the genus Brucella spp, which causes productive losses in large animals. It was observed that the practical activities and the active methodology contributed for the students to be able to answer the problem solution that, at first, was seen by them as an enigma and at the same time as a challenge in the search for a solution. Thus, it is suggested that such activity be applied in different disciplines, with the function of developing the students' autonomy in the face of the adversities that they may face in their professional life.